(untitled) (Journal of actual problems of jurisprudence, 2018)
The problem of property rights is a category at all times attracted the attention of science and pravoprmenitelnoy practice. Some of the legal institutions that need to more clearly define the concepts and features include Institute of property rights and other rights. Despite the huge number of attempts to define property law, it is not generally accepted in the science achieved neither civil law nor in the current legislation. “Triad” concept of property law appeals to the appropriate authority of the - the possession, use and disposal. In various kinds of property law right holder has a different set of powers. The most common definition of signs of property rights is reflected in the amount of its specific features. Marked heterogeneity of the various attributes of property rights, as well as the fragility of the boundaries between proprietary and Obligations Act, due prisuschestyu individual traits and both. Key words: law, property law, possessions, signs, powers.